STRATEGI GURU DALAM MENGUATKAN MINAT BELAJAR SISWA KELAS IV SD NEGERI KLUMPIT PADA PEMBELAJARAN IPA - Desy Ariyanti Indah Wijayanti; Wawan Shokib Rondli; F. Shoufika Hilyana (STKIP Subang, 2022)
This study aims to describe the teacher's strategy in strengthening student interest in learning, and describe the factors that inhibit and support teachers in strengthening the learning interest of fourth grade students at SD Negeri Klumpit in science learning. The research was conducted at SD Negeri Klumpit, Tlogowungu District, Pati Regency, by taking the subject of teachers and fourth grade students. In this study used qualitative research methods and types of case study approaches as well as data collection techniques that include the stages of observation, interviews, and documentation. The results showed that the strategies used by teachers in strengthening interest in learning in science learning were establishing agreements, designing the learning expected by students, creating positive competencies, creating threat-free classes, giving appreciation to students, and encouraging students to reflect on learning. While the supporting factors that influence the teacher's strategy are the agreement that all students agree on, the existence of science learning videos, the existence of learning designs that are packaged by playing and singing, and the appreciation of students. The factors that influence the implementation of the teacher's strategy include the driving factor with an agreement agreed upon by all students, the existence of science learning videos, the existence of learning designs that are packaged by playing and singing, as well as appreciation of students. While the inhibiting factors are the lack of preparation in delivering the material and the lack of giving students a sense of self. Keywords: Teacher strategy, Ask to learn, Science Learning